2014
DOI: 10.1016/j.carbpol.2014.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amylose:amylopectin ratio and rice bran addition on starch films properties

Abstract: The influence of the amylose:amylopectin ratio on the properties of pea, potato and 30 cassava starch (with a high, intermediate and low amylose-amylopectin ratio, 31 respectively) films and the effect of the incorporation of rice bran of two different 32 particle sizes were studied. The structural, mechanical (elastic modulus, tensile 33 strength and percentage of elongation at break), optical (gloss and internal 34 transmittance) and barrier (water vapour permeability and oxygen permeability) 35properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
111
1
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 39 publications
20
111
1
5
Order By: Relevance
“…It has a granular structure and is composed of two macromolecules: amylose and amylopectin. Amylose is a linear polymer formed by glucose units linked by α-(1,4) whereas amylopectin is a highly branched polymer of glucose units with ramifications in α-(1,6) [35,36]. However, due to their hydrophilicity starch-based films/coatings exhibit water solubility and poor water vapour barrier properties [10].…”
Section: Starch-based Coatings For the Preservation Of Fruits And Vegmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a granular structure and is composed of two macromolecules: amylose and amylopectin. Amylose is a linear polymer formed by glucose units linked by α-(1,4) whereas amylopectin is a highly branched polymer of glucose units with ramifications in α-(1,6) [35,36]. However, due to their hydrophilicity starch-based films/coatings exhibit water solubility and poor water vapour barrier properties [10].…”
Section: Starch-based Coatings For the Preservation Of Fruits And Vegmentioning
confidence: 99%
“…In this sense, the adequate compatibilization of lipids and polymers and the final size distribution of lipid particles in the film also affect the coating's functional properties [44]. As concerns starch coatings, the amylose-amylopectin ratio affected their functionality due to the different structure of the films generated with high-amylose starch, where linear amylose, with regions of helical conformation, exhibited better packed domains in the matrix that is more crystalline in nature [36]. The authors of [37] found that coatings made with high-amylose starch better preserved the weight losses and firmness of strawberries for longer periods than coatings of medium-amylose starch.…”
Section: Strawberrymentioning
confidence: 99%
“…One part of the samples was stored under the same conditions for five weeks in order to perform the second series of analysis of stored films (Cano et al, 2014).…”
Section: Preparation Of Film-forming Dispersions and S:pva Blend Filmsmentioning
confidence: 99%
“…Native starch has a granular structure and presents different properties depending on its amylose/amylopectin ratio. Gelatinized starch shows a great filmforming capacity and, as is well known, its two macromolecules are responsible for starch recrystallization, which leads to changes in the mechanical response of starch-based films (Cano et al, 2014;Jiménez et al, 2012a;Talja et al, 2007). Besides their poor mechanical properties, starch films are highly hydrophilic in nature, which confers a great water vapour sensitivity and poor water barrier properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation